The Managing Director's Global Policy Agenda : Decisive Action, Durable Growth. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2016)
Full text also available in: Arabic, Chinese, French, Japanese, Russian, and Spanish. The global economy is expanding moderately but the outlook has weakened further since October, and risks have increased. The global economy has been impaired from growth that has been too slow for too long, and at this rate a sustained recovery-with the expected higher living standards, lower unemployment and declining debt levels-may not be delivered. However, some recent improvement in data releases, somewhat firmer oil prices, reduced pressures on outflows from China, and actions by major central banks have all contributed to improving sentiment. Building on these recent positive developments, the global economy can get back on a stronger and safer track, but the current policy response will need to go further. Countries must reinforce their commitment to durable global growth and employ a more potent policy mix. A three-pronged approach with monetary, fiscal, and structural actions can work as a virtuous trinity, lifting actual and potential growth, averting recession risks, and enhancing financial stability. The IMF will support this commitment by helping countries identify space, craft appropriate policies, and build capacity to deliver on these policies; providing a strong financial backstop for policy implementation; and assisting members with new challenges.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: China, People's Republic of